KOMUNIKASI POLITIK DALAM FUNGSI BUDGETING DPRD KABUPATEN INDRAGIRI HULU - Andi Kardian Riva'i (Dialektika, 2020)
The purpose of this study is to gain an understanding and know the factors that influence political communication and budgeting functions of the Indragiri Hulu District Parliament. Research informants numbered 6 people who were determined through incidental sampling. The results of this study indicate that in the determination of the budget, Indragiri Hulu Regency DPRD through the Budget Agency together with the Regional Government Budget Team (TPAD) agreed on the General Budget Policy - Priority Budget Ceiling (KUA-PPAS) based on the budget guidebook. Political communication in the budget function has a distinctive form, strategy, media and activity, political construction that leads to interests built on the reality of knowledge, public awareness, public discourse resulting from the political construction of budget management, the relationship between government spending and regional revenues so the budgeting function works based on fiscal policy, the allocation function and the principle of equitable development. The APBD also forms the basis for regional financial control, inspection and supervision activities as seen from the budget cycle of the APBD budget which starts on January 1 and ends on December 31 of the year concerned consisting of the preparation and stipulation of 1 year before the fiscal year, implementation 1 year during the year current budget and APBD accountability reports. Keynote: Political Communication, Budget Function, Indragiri Hulu Regency DPRD